Hierarchical porous polymer sponge large-scale preparation method and application

CN122958758APending Publication Date: 2026-10-23SHANGHAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611411291.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0006]针对现有三维太阳能蒸发器中毛细供水与水力阻力难以兼顾、极易引发盐结晶,且现有多尺度流体通道的构建方法(如定向冷冻、3D打印)往往工艺复杂、依赖精密设备,现有一步法工艺多需分步交联或后续处理、难以真正实现单工序规模化生产等技术缺陷,本发明的目的在于提供一种分层多孔聚合物海绵及其规模化制备方法和应用

Benefits of technology

[0024]与现有技术相比,本发明具有以下显著的有益效果:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958758A_ABST
    Figure CN122958758A_ABST
Patent Text Reader

Abstract

The application discloses a layered porous polymer sponge large-scale preparation method and application. A one-step bubble template method is adopted, and a basic hydrophilic polymer, a multifunctional pore regulator, a crosslinking agent, a photothermal agent and a catalyst are mixed in water phase at one time, and after mechanical foaming, the mixture is subjected to hot curing and demolding, and the whole process does not need step-by-step crosslinking, template removal or subsequent etching process. The core lies in the reaction kinetics regulation of the multifunctional pore regulator, which can not only be used as a surfactant to stabilize bubbles, but also can competitively combine with the crosslinking agent to delay the crosslinking kinetics of the main polymer network and prolong the bubble coalescence time window. Through the mechanism, the sponge is in-situ constructed with low-resistance large pores, the photothermal agent is simultaneously anchored on the pore wall of high-capillary micropores, and a layered porous structure with multiple scales is formed in a single step. The process is extremely simple, one-step forming and does not depend on large and precise equipment, and the obtained sponge has high efficient capillary water transport, low hydraulic resistance and mechanical resilience, and is easy to be deployed in low-cost large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of porous polymer materials and mass transfer engineering. Specifically, it relates to a method for the large-scale preparation of a layered porous polymer sponge, and the application of the sponge in rapid fluid transport, photothermal interfacial evaporation seawater desalination, and high-salinity wastewater treatment. Background Technology

[0002] Solar-driven interfacial evaporation technology utilizes renewable solar energy to achieve localized heating and water vapor conversion, demonstrating enormous application potential in seawater desalination and wastewater treatment. In recent years, in order to overcome the limitation of the surface area of ​​traditional two-dimensional (2D) planar evaporators and further improve the efficiency of environmental energy harvesting, the design of evaporators has gradually evolved from two-dimensional planes to three-dimensional (3D) structures.

[0003] However, 3D evaporators face severe fluid transfer bottlenecks in practical applications. As the height of the 3D evaporator increases, water needs to overcome greater gravitational potential energy to be transported to the top evaporation interface, placing extremely high demands on the material's capillary water supply capacity. In conventional porous materials, there is an inherent physical trade-off between capillary suction and hydraulic resistance: to obtain stronger capillary lifting force to increase the water supply height, the pore size of the material usually needs to be reduced; however, reducing the pore size drastically increases the fluid transport resistance within the pores. This contradiction between water supply height and transport resistance leads to the problem of insufficient top water supply and severely delayed fluid transport in tall 3D evaporators. More seriously, when processing high-salinity fluids, limited top water supply can easily lead to localized supersaturation of solute concentration at the evaporation interface, triggering severe salt crystallization. The precipitated salt quickly covers the photothermal absorption layer and clogs the pores, ultimately causing the complete failure of the entire evaporation system.

[0004] To overcome the constraints between microscopic capillary forces and macroscopic hydraulic resistance, existing conventional solutions mainly mimic the multi-scale water transport network of the xylem in natural trees, constructing layered porous channels with a synergistic effect of macroscopic macropores and microscopic micropores. Currently, this field primarily relies on advanced manufacturing technologies such as directional cryogenic casting or 3D printing to construct such multi-scale hydraulic channels; some one-step graded porous materials rely on multi-stage stepwise cross-linking or require subsequent removal of templates / porogens, making it difficult to truly achieve single-process batch molding.

[0005] While the aforementioned conventional solutions have demonstrated the feasibility of alleviating the conflict between water supply and resistance in theoretical and laboratory tests, existing technologies generally suffer from the following insurmountable problems: directional cryogenic casting and 3D printing manufacturing processes are extremely cumbersome, heavily reliant on precise and expensive temperature control or molding equipment; existing one-step processes generally suffer from incomplete workflows and require additional post-processing; furthermore, these processes have stringent requirements on the physicochemical properties of the polymer substrate, making them unsuitable for the rapid prototyping of complex or large-volume three-dimensional parts. These inherent limitations make the manufacturing cost of existing layered porous materials extremely high, hindering low-cost, large-scale mass production and significantly impeding the practical engineering deployment of 3D solar evaporators. Summary of the Invention

[0006] To address the shortcomings of existing three-dimensional solar evaporators, such as the difficulty in balancing capillary water supply and hydraulic resistance, the high risk of salt crystallization, and the complexity and reliance on precision equipment in constructing multi-scale fluid channels (e.g., directional freezing, 3D printing), as well as the limitations of existing one-step processes requiring stepwise crosslinking or post-processing, hindering large-scale single-process production, this invention aims to provide a layered porous polymer sponge and its large-scale preparation method and applications. This invention utilizes a one-step bubble template process integrating single-step feeding and mixing, mechanical foaming, and in-situ crosslinking to successfully construct a layered pore network with synergistic macropores and micropores. This allows for in-situ formation of a hierarchical pore structure without stepwise reactions or post-processing, overcoming the mass production limitations of existing technologies at the underlying preparation stage and breaking through the physical limitations of fluid transport at the material structure level.

[0007] 1. Technical Solution

[0008] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for the large-scale preparation of layered porous polymer sponges, comprising the following steps: S1. Mix the first hydrophilic polymer, multifunctional pore regulator, photothermal conversion material, aldehyde crosslinking agent and water evenly to obtain a precursor solution; S2. Mechanically foam the precursor solution to form a stable foam emulsion; S3. Then, an acidic catalyst is added to the foam emulsion, and the emulsion is poured into the mold in batches. S4. In-situ thermosetting crosslinking reaction is carried out in the mold; S5. Obtain a layered porous polymer sponge with interconnected macropores and micropores in the pore walls.

[0009] By employing the above technical solution, the first hydrophilic polymer and the aldehyde crosslinking agent undergo an acetalization reaction under acidic conditions, gradually constructing a three-dimensional crosslinked network. The active amino groups in the multifunctional pore regulator competitively bind with the aldehyde groups, consuming some of the crosslinking agent and significantly reducing the crosslinking rate of the main network, allowing the system to maintain a low viscosity for a longer period. Within this time window, the bubbles introduced by mechanical foaming continuously coalesce, and the liquid film between adjacent bubbles ruptures, forming larger interconnected channels. The multifunctional pore regulator molecules adsorb at the gas-liquid interface, inhibiting bubble rupture or collapse before thermal curing. The photothermal conversion material is uniformly dispersed in the continuous phase, enriched in the pore wall region as the bubbles coalesce, and locked inside the pore walls during the crosslinked network formation process. Ultimately, a microporous structure is formed in the pore walls, which, together with the macropores, constitute an interconnected hierarchical porous structure. The entire process requires only a single casting and curing to complete the in-situ construction of the hierarchical pore structure, without any intermediate processing steps.

[0010] Furthermore, the multifunctional pore regulator is composed of a second hydrophilic polymer. Preferably, the second hydrophilic polymer is a water-soluble polymer rich in amino groups, selected from one or more of water-soluble chitosan, polyacrylamide, polyethyleneamine, polyethyleneimine, polylysine, or polyamide-amine dendritic macromolecules.

[0011] By employing the above technical solution, the primary and secondary amine groups in the second hydrophilic polymer undergo nucleophilic addition and condensation reactions with the aldehyde crosslinking agent, consuming the aldehyde groups in the system. This reaction preferentially occurs over the acetalization reaction of the first hydrophilic polymer, thereby reducing the number of crosslinking points in the main network, prolonging the crosslinking induction period, and providing sufficient time for bubble polymerization. Simultaneously, the second hydrophilic polymer adsorbs onto the bubble surface, reducing interfacial tension and stabilizing the foam. Its amino group density and chain flexibility affect the degree of crosslinking delay and foam stability, thereby controlling the macropore size and pore wall thickness.

[0012] Further, the first hydrophilic polymer is selected from one or more of polyvinyl alcohol, cellulose derivatives, or sodium alginate, preferably polyvinyl alcohol; the photothermal conversion material is selected from one or more of carbon nanotubes, carbon black, graphite powder, graphene oxide, polypyrrole, or pyrrole-2-carboxaldehyde; the aldehyde crosslinking agent is selected from one or more of formaldehyde, glutaraldehyde, or glyoxal; and the acidic catalyst is selected from one or more of sulfuric acid, hydrochloric acid, nitric acid, or acetic acid.

[0013] Furthermore, in the preparation method, the amounts of each component added, based on 1 part by weight of water, are as follows: The mass of the first hydrophilic polymer is 0.05 to 0.20 parts, preferably 0.05 to 0.10 parts; In the multifunctional pore regulator, the mass of the second hydrophilic polymer is 0.01~0.15 parts, preferably 0.02~0.05 parts; The mass of the photothermal conversion material is 0.005~0.1 parts, preferably 0.01~0.05 parts; The mass of the aldehyde crosslinking agent is 0.01 to 0.15 parts, preferably 0.02 to 0.05 parts; The mass of the acidic catalyst is 0.01 to 0.3 parts, preferably 0.1 to 0.2 parts.

[0014] By adopting the above technical solution, the first hydrophilic polymer serves as the main body of the sponge skeleton, and its dosage determines the initial viscosity of the continuous phase and the number of crosslinking points that can be formed. If the dosage is too low, the crosslinking network is sparse, and the bubble walls are prone to rupture or collapse; if the dosage is too high, the system viscosity is too high, making it difficult for bubbles to disperse uniformly and hindering aggregation. The ratio of the multifunctional pore regulator to the first hydrophilic polymer determines the degree of competitive binding. Increasing the ratio leads to the consumption of more aldehyde groups, reducing the crosslinking rate of the main network, prolonging the bubble aggregation time, and increasing the macropore size; decreasing the ratio accelerates crosslinking but reduces the macropore size. Excessive addition of photothermal conversion material easily forms agglomerates, reducing light absorption efficiency and damaging foam stability. Matching the dosage of the aldehyde crosslinking agent and the acidic catalyst ensures that the crosslinking reaction is completed within a suitable timescale, keeping the foam stable before thermal curing and forming a continuous and complete pore wall structure after curing.

[0015] Furthermore, the conditions for mechanical foaming include: a mechanical stirring speed of 8000~20000 rpm, preferably 10000~15000 rpm; and a mechanical stirring time of 5~30 min, preferably 10~20 min.

[0016] By employing the above technical solution, mechanical stirring introduces air into the liquid phase through shear force, forming a large number of bubbles. The stirring intensity determines the input energy density; lower intensity results in fewer bubbles with a wide size distribution, making it difficult to obtain uniform foam; excessively high intensity leads to severe bubble breakage, and the system's temperature rise may cause premature local cross-linking. Stirring time affects the degree of bubble aggregation and the foam volume fraction; too short a time results in insufficient macropore connectivity, while too long a time makes the foam prone to collapse. Reasonable control of shear intensity and stirring time can ensure the foam remains stable and forms a uniform macroporous structure before thermal curing.

[0017] Furthermore, the conditions for the in-situ thermosetting crosslinking reaction include: a reaction temperature of 20~80 °C, preferably 40~70 °C, more preferably 60 °C; and a reaction time of 1~72 h, preferably 2~24 h, more preferably 2~12 h.

[0018] By employing the above technical solution, the thermosetting stage completes the cross-linking reaction and fixes the pore structure. Increased temperature accelerates the reaction rate of aldehyde groups with hydroxyl and amino groups, enabling the rapid formation of the cross-linked network and fixing the bubble structure. Excessively high temperatures accelerate liquid film drainage, causing pore walls to thin or even rupture, and easily leading to uneven cross-linking; excessively low temperatures result in slow cross-linking, prolonged liquid drainage and aggregation of the foam, leading to uncontrolled pore size. In the presence of an acidic catalyst, the acetalization reaction proceeds efficiently at a mild temperature. After appropriate heat preservation, the cross-linked network fully develops, resulting in a sponge with a stable pore structure, good wet resilience, and good dimensional stability.

[0019] Furthermore, after the in-situ thermosetting crosslinking reaction is completed, the process further includes: taking out the obtained sponge and washing it repeatedly with a washing solution until the pH value of the washing solution is neutral, and then drying it.

[0020] Secondly, the present invention provides a layered porous polymer sponge prepared by the above-described method. The layered porous polymer sponge has an internal layered structure in which macropores and micropores are interconnected, wherein the macropores have a diameter of 100-200 μm and the micropores have a diameter of 1-3 μm.

[0021] Thirdly, in the one-step bubble template method provided by this invention, the container for the in-situ thermosetting crosslinking reaction is a mold of various shapes, including cylinders, cones, cubes or 3D irregular containers. The container material can be polymer, glass, ceramic or metal containers, and the container volume is upgraded to the cubic level. After the reaction is completed, the container is demolded.

[0022] Fourthly, the present invention provides the application of the above-mentioned layered porous polymer sponge in solar interface water evaporation, seawater desalination or high-salt wastewater treatment.

[0023] 2. Beneficial effects of the invention

[0024] Compared with the prior art, the present invention has the following significant advantages: Overcoming the equilibrium effect of fluid transport to achieve high-flux water delivery: This invention constructs a layered structure with synergistic micropores (1~3 μm) and interconnected macropores (100~200 μm) through unique component design and foaming control. The micropore network provides strong capillary suction, while the through-hole macropore network minimizes hydraulic transport resistance. This structure completely overcomes the diffusion limitations faced by traditional uniform microporous materials when increasing water supply height, achieving high-flux water transport.

[0025] Excellent resistance to salt crystallization and long-term operational stability: When applied to photothermal evaporation in high-salinity water bodies, the continuous macroporous network inside the material provides ample physical space for the three-dimensional reflux and ion convection diffusion of high-concentration brine. This structure spatially separates the upward water transport from the downward salt removal process, enabling the evaporator to effectively prevent salt accumulation during continuous processing of high-concentration brine and achieve long-term stable freshwater production.

[0026] A one-step in-situ construction method for hierarchical pore structures is extremely simple and scalable: The preparation method of this invention abandons complex processes such as cryogenic casting or 3D printing that rely on expensive equipment. It only requires simple mechanical stirring and foaming at room temperature and pressure, followed by in-situ thermosetting and cross-linking using a mold to achieve one-step molding. This process has high substrate compatibility, low cost, and can easily adapt to casting molds of any shape. The mold volume can be easily scaled up to the liter and cubic level, possessing extremely strong prospects for industrial mass production. Attached Figure Description

[0027] Figure 1 The flowchart of the one-step preparation process of a layered porous polymer sponge provided by the present invention shows the process steps in sequence: preparing the precursor solution, mechanical foaming, adding an acidic catalyst and batch casting, in-situ thermosetting crosslinking reaction, and obtaining the final sponge.

[0028] Figure 2 The image shows a scanning electron microscope (SEM) image of the microstructure of the layered porous polymer sponge provided in Example 1 of this invention, along with a statistical diagram of the distribution of macropore and micropore size. This verifies the layered structure of a network of macropores (100~200 μm) combined with a dense micropore (1~3 μm) network formed by a kinetic regulation mechanism. Figure 3 The image shows the microstructure of Comparative Example 1 (a traditional sponge material lacking multifunctional pore conditioners) as a scanning electron microscope (SEM) image and a statistical diagram of the pore size distribution of individual micropores; it demonstrates its conventionally constrained and uniformly sized microporous network structure. Figure 4 The graph shows a comparison of the dynamic test curves of the water rise height over time between the layered porous polymer sponge prepared in Example 1 of the present invention and the conventional sponge material in Comparative Example 1; it verifies that Example 1 significantly improves capillary conduction performance by breaking the balance effect between capillary water supply and hydraulic resistance. Figure 5 The photos show the layered porous polymer sponge prepared in Example 1 of this invention undergoing extreme compression, torsion, and tension, as well as large strain mechanical deformation tests and shape memory functions; these tests verify the material's excellent mechanical resilience and practical deployment properties. Figure 6The diagram shows the change curve of the interfacial evaporation rate of the layered porous sponge of Example 1 of the present invention with the conventional sponge material of Comparative Example 1 when treating real seawater (36 hours of continuous operation) and the optical photograph of the top of the corresponding device. The results show that Comparative Example 1 suffered from water shortage and shrinkage at the top due to limited diffusion and severe salt crystallization, while the layered porous network of Example 1 achieved spatial decoupling of salt, thereby maintaining a stable evaporation rate and preventing crystal precipitation. Figure 7 The bar chart shows the interfacial evaporation rate of the layered porous polymer sponge prepared in Example 1 of the present invention under different salt types and salinity conditions. The results show that the evaporation rate of all samples remains highly stable, verifying the material's excellent high salt universality and anti-scaling ability. Figure 8 The diagram shows the interfacial evaporation rate test of the layered porous polymer sponge prepared in Example 1 of this invention during multiple cycles of treating real seawater (showing the state of the lamp being on / off in each cycle); demonstrating that the material's photothermal absorption and salt resistance and desalination performance remain highly stable under periodic operation conditions. Figure 9 The schematic diagram of the process for preparing layered porous polymer sponge by the one-step bubble template method provided by the present invention shows the preparation steps of precursor solution preparation, mechanical stirring and foaming, casting into mold, in-situ thermosetting crosslinking and demolding to obtain the final sponge. Detailed Implementation

[0029] The present application will be further described in detail below with reference to embodiments and comparative examples. Unless otherwise specified, the experimental methods used below are conventional methods. Unless otherwise specified, the materials, reagents, methods and instruments used are all conventional materials, reagents, methods and instruments in the art, which can be obtained by those skilled in the art through commercial channels or prepared according to literature methods.

[0030] Example 1: 1 g of polyvinyl alcohol, 3.0 g of water-soluble chitosan, 1.5 g of pyrrole-2-carboxaldehyde, and 0.2 g of formaldehyde solution were weighed and continuously stirred to prepare a homogeneous precursor solution. The precursor solution was subjected to vigorous mechanical foaming at 12,000 rpm for 15 minutes using a high-speed homogenizer to form a multiphase foam emulsion. 1 g of sulfuric acid solution was added to the foam emulsion under continuous low-speed stirring. The mixed foam solution was then quickly poured into a cylindrical mold and subjected to in-situ acid-catalyzed thermosetting crosslinking at 60°C for 4 hours. The resulting sponge was repeatedly washed and squeezed in deionized water until the pH of the washing solution reached 7. Finally, it was freeze-dried to obtain an integral sponge with a layered porous structure.

[0031] Example 2: 1 g of polyvinyl alcohol, 3.0 g of polyethyleneimine, 1.5 g of pyrrole-2-carboxaldehyde, and 0.2 g of formaldehyde solution were weighed and continuously stirred to prepare a homogeneous precursor solution. The precursor solution was subjected to vigorous mechanical foaming at 12,000 rpm for 15 minutes using a high-speed homogenizer to form a multiphase foam emulsion. 1 g of sulfuric acid solution was added to the foam emulsion under continuous low-speed stirring. The mixed foam solution was then quickly poured into a cubic mold and subjected to in-situ acid-catalyzed thermosetting crosslinking at 60°C for 4 hours. The resulting sponge was repeatedly washed and squeezed in deionized water until the pH of the washing solution reached 7. Finally, it was freeze-dried to obtain an integral sponge with a layered porous structure.

[0032] Example 3: 1 g of polyvinyl alcohol, 3.0 g of polyvinylamine, 1.5 g of pyrrole-2-carboxaldehyde, and 0.2 g of formaldehyde solution were weighed and continuously stirred to prepare a homogeneous precursor solution. The precursor solution was subjected to vigorous mechanical foaming at 12,000 rpm for 15 minutes using a high-speed homogenizer to form a multiphase foam emulsion. 1 g of sulfuric acid solution was added to the foam emulsion under continuous low-speed stirring. The mixed foam solution was then quickly poured into a cylindrical mold and subjected to in-situ acid-catalyzed thermosetting crosslinking at 60°C for 4 hours. The resulting sponge was repeatedly washed and squeezed in deionized water until the pH of the washing solution reached 7. Finally, it was freeze-dried to obtain an integral sponge with a layered porous structure.

[0033] Example 4: 1 g of polyvinyl alcohol, 3.0 g of polylysine, 1.5 g of pyrrole-2-carboxaldehyde, and 0.2 g of formaldehyde solution were weighed and continuously stirred to prepare a homogeneous precursor solution. The precursor solution was subjected to vigorous mechanical foaming at 12,000 rpm for 15 minutes using a high-speed homogenizer to form a multiphase foam emulsion. 1 g of sulfuric acid solution was added to the foam emulsion under continuous low-speed stirring. The mixed foam solution was then quickly poured into a cubic mold and subjected to in-situ acid-catalyzed thermosetting crosslinking at 60 °C for 4 hours. The resulting sponge was repeatedly washed and squeezed in deionized water until the pH of the washing solution reached 7. Finally, it was freeze-dried to obtain an integral sponge with a layered porous structure.

[0034] Example 5: 1 g of polyvinyl alcohol, 3.0 g of polylysine, 1.5 g of graphite powder, and 0.2 g of formaldehyde solution were weighed and continuously stirred to prepare a homogeneous precursor solution. The precursor solution was subjected to vigorous mechanical foaming at 12,000 rpm for 15 minutes using a high-speed homogenizer to form a multiphase foam emulsion. 1 g of sulfuric acid solution was added to the foam emulsion under continuous low-speed stirring. The mixed foam solution was then quickly poured into a conical mold and subjected to in-situ acid-catalyzed thermosetting crosslinking at 60°C for 4 hours. The resulting sponge was repeatedly washed and squeezed in deionized water until the pH of the washing solution reached 7. Finally, it was freeze-dried to obtain an integral sponge with a layered porous structure.

[0035] Example 6: 1 g of polyvinyl alcohol, 3.0 g of polylysine, 1.5 g of carbon nanotubes, and 0.2 g of formaldehyde solution were weighed and continuously stirred to prepare a homogeneous precursor solution. The precursor solution was subjected to vigorous mechanical foaming at 12,000 rpm for 15 minutes using a high-speed homogenizer to form a multiphase foam emulsion. 1 g of sulfuric acid solution was added to the foam emulsion under continuous low-speed stirring. The mixed foam solution was then quickly poured into a mold and subjected to in-situ acid-catalyzed thermosetting crosslinking at 60 °C for 4 hours. The resulting sponge was repeatedly washed and squeezed in deionized water until the pH of the washing solution reached 7. Finally, it was freeze-dried to obtain an integral sponge with a layered porous structure.

[0036] Example 7: 1 g of polyvinyl alcohol, 3.0 g of polylysine, 1.5 g of polypyrrole, and 0.2 g of formaldehyde solution were weighed and continuously stirred to prepare a homogeneous precursor solution. The precursor solution was subjected to vigorous mechanical foaming at 12,000 rpm for 15 minutes using a high-speed homogenizer to form a multiphase foam emulsion. 1 g of sulfuric acid solution was added to the foam emulsion under continuous low-speed stirring. The mixed foam solution was then quickly poured into a cylindrical mold and subjected to in-situ acid-catalyzed thermosetting crosslinking at 60 °C for 4 hours. The resulting sponge was repeatedly washed and squeezed in deionized water until the pH of the washing solution reached 7. Finally, it was freeze-dried to obtain an integral sponge with a layered porous structure.

[0037] Example 8: 1 g of polyvinyl alcohol, 3.0 g of polylysine, 1.5 g of graphene oxide, and 0.2 g of formaldehyde solution were weighed and continuously stirred to prepare a homogeneous precursor solution. The precursor solution was subjected to vigorous mechanical foaming at 12,000 rpm for 15 minutes using a high-speed homogenizer to form a multiphase foam emulsion. 1 g of sulfuric acid solution was added to the foam emulsion under continuous low-speed stirring. The mixed foam solution was then quickly poured into a cylindrical mold and subjected to in-situ acid-catalyzed thermosetting crosslinking at 60 °C for 4 hours. The resulting sponge was repeatedly washed and squeezed in deionized water until the pH of the washing solution reached 7. Finally, it was freeze-dried to obtain an integral sponge with a layered porous structure.

[0038] Example 9: 1 kg of polyvinyl alcohol, 3.0 kg of polylysine, 1.5 kg of graphene oxide, and 0.2 kg of formaldehyde solution were weighed and continuously stirred to prepare a homogeneous precursor solution. The precursor solution was subjected to vigorous mechanical foaming at 12000 rpm for 30 minutes using a high-speed homogenizer to form a multiphase foam emulsion. While continuously stirring at low speed, 1 kg of sulfuric acid solution was slowly added to the foam emulsion. The mixed foam solution was then quickly poured into the mold matrix of Example 8, with the number of molds being 1000 times that of Example 8, and the matrix arrangement being 10. 10, a total of 10 matrices. In-situ acid-catalyzed thermosetting cross-linking was performed at 60 ℃ for 4 hours; the resulting sponge was repeatedly washed and squeezed in deionized water until the pH of the washing solution reached 7, and finally freeze-dried to obtain an integral sponge matrix with a layered porous structure. The overall mixing, curing reaction, and demolding time increased by 30% compared to scheme 8.

[0039] Comparative Case 1: 1 g of polyvinyl alcohol, 1.5 g of pyrrole-2-carboxaldehyde, and 0.2 g of formaldehyde solution were weighed and continuously stirred to prepare a homogeneous precursor solution; the precursor solution was subjected to vigorous mechanical foaming at 12000 rpm for 15 minutes using a high-speed homogenizer to form a multiphase foam emulsion; 1 g of sulfuric acid solution was added to the foam emulsion under continuous low-speed stirring; the mixed foam liquid was then quickly poured into a mold and subjected to in-situ acid-catalyzed thermosetting crosslinking at 60 °C for 4 hours; the resulting sponge was repeatedly washed and squeezed in deionized water until the pH of the washing solution reached 7, and finally freeze-dried to obtain a traditional uniform microporous polymer sponge.

[0040] Performance testing methods

[0041] To verify the technical effect of the present invention, the following performance tests were conducted on the sponge materials prepared in the above embodiments and comparative examples: (1) Microscopic morphology and pore size test: The internal pore structure of the freeze-dried sponge was observed by scanning electron microscope (SEM), and the pore size distribution was statistically analyzed by image analysis software.

[0042] (2) Hydraulics and capillary conduction test: The sponge sample is suspended vertically with its bottom end in contact with deionized water, and the curve of water rise height over time is recorded.

[0043] (3) Mechanical properties and shape memory test: The sponge in a fully hydrated state was subjected to stretching, torsion, and deformation recovery behavior before and after compression.

[0044] (4) Photothermal interface evaporation performance test: under one standard solar irradiance (1 kW m - ²) Under these conditions, sponge materials were placed in salt water with different salinity, different salt types, and real seawater, and the mass change during the continuous evaporation process was recorded to calculate the evaporation rate.

[0045] (5) Long-term stability test against salt crystallization: at 1 kW m - ²Under continuous or periodic (on / off cycle) light conditions, place the sponge in a high-concentration salt solution (such as 20 wt% NaCl or real seawater) for more than 36 hours, observe the salt crystallization on the top surface of the evaporator, and record the decay of the evaporation rate in real time.

[0046] Analysis of test results in conjunction with the attached diagram

[0047] Please see Figure 2 and Figure 3 ,pass Figure 2 and Figure 3 The comparison shows that the sponge material in Example 1 successfully constructed a perfect layered structure consisting of interconnected macropores (100~200 μm) and wall micropores (1~3 μm); while Comparative Example 1, lacking a multifunctional pore regulator, only exhibits uniformly sized and height-limited micropores (~3 μm). The effect to be demonstrated by the attached figure is that this invention, by introducing a multifunctional pore regulator, successfully utilizes reaction kinetic retardation and bubble coalescence mechanisms to achieve a one-step innovative underlying structure of a multi-scale water transport network without relying on complex freezing or 3D printing equipment.

[0048] Please see Figure 4 ,pass Figure 4As can be seen, the capillary ascent dynamics of the sponge in Example 1 exhibit an exponential increase, reaching a high level and rapidly saturating within a very short time at the wetting front; while the capillary ascent in Comparative Example 1 stagnates at a low height. The effect to be demonstrated by the attached figure is that the layered porous structure of the present invention completely breaks the trade-off between capillary suction force and hydraulic resistance in traditional materials. The large-pore network minimizes hydraulic resistance, thereby achieving rapid water transport over large flow rates and long distances.

[0049] Please see Figure 5 ,pass Figure 5 As can be seen, the sponge in Example 1 can still achieve almost complete recovery after undergoing extreme torsion, stretching, and compression. The effect to be demonstrated by the attached figure is that the cross-linked polymer skeleton of the present invention has excellent mechanical toughness and shape memory function, fundamentally overcoming the defects of traditional hydrogels or porous materials that are fragile and prone to structural collapse, and providing structural protection for long-term water treatment operations and high-density compact storage.

[0050] Please see Figure 6 ,pass Figure 6 As can be seen, in the 36-hour continuous evaporation test of real seawater, the evaporation rate of Comparative Example 1 decreased significantly due to limited diffusion, and the top showed signs of shrinkage due to water shortage; while the evaporation rate of Example 1 remained stable throughout, and no crystals precipitated on the surface. The effect to be demonstrated in the attached figure is that the layered porous structure of the present invention achieves spatial decoupling between the upward transport of water and the downward diffusion of high-concentration salt. Micropores ensure water supply, while macropores provide channels for salt removal, solving the technical problem of easy crystallization and blockage during the evaporation of high-salt water from the underlying physical mechanism.

[0051] Please see Figure 7 and Figure 8 ,pass Figure 7 and Figure 8 As can be seen, the sponge of Example 1 exhibits extremely excellent stability in evaporation rate when faced with different types of salt solutions (salt concentration of 3.5 wt.%), high salt concentrations (even extreme salinity of 20 wt.%), and in multiple "day and night" cycle tests. The effect to be demonstrated in the attached figure is that the material system of this invention has extremely strong environmental adaptability and long-term anti-scaling ability, fully meeting the requirements for long-term continuous operation in real, complex marine or industrial wastewater environments.

[0052] In summary, the layered porous polymer sponge of the present invention exhibits the following comprehensive performance characteristics: (1) Excellent macroscopic hydraulic conductivity: Through a unique dynamic control preparation process, the sponge of the present invention breaks through the diffusion limitation of traditional microporous materials, exhibits a fast capillary climbing speed, and provides a continuous and sufficient water supply for the towering 3D evaporator.

[0053] (2) High efficiency and long-term stable salt evaporation resistance: Thanks to the spatial decoupling mechanism in the structure, the sponge of the present invention can not only maintain a very high photothermal evaporation flux in an extreme high salinity environment of up to 20 wt.% NaCl, but also completely suppress salt crystallization at the evaporation interface in the process, ensuring the maintenance-free nature of the material under long-term operation.

[0054] (3) Excellent mechanical toughness and shape recovery ability: The rich cross-linking and hydrogen bonding within the polymer network enable the sponge to withstand large strain damage in a fully hydrated state and recover its shape in a timely manner, thus possessing shape memory function, which greatly facilitates the transportation and deployment of materials.

[0055] (4) The large-scale preparation process is simple, and molds of conventional materials and sizes can be used to scale up the materials.

[0056] The innovations of this invention are mainly reflected in the following aspects: (1) Innovative preparation mechanism (kinetic regulation): This invention innovatively introduces a multifunctional pore regulator (such as an amino-rich polymer). It not only acts as a surfactant to stabilize bubbles, but more importantly, it competes with aldehyde crosslinking agents for binding. This "crosslinking agent grabbing" mechanism effectively delays the curing rate of the main network, providing a valuable time window for bubbles to coalesce into macropores. This is a novel pore-forming regulation strategy at the molecular dynamics level.

[0057] (2) Material structure innovation (layered network): This invention abandons expensive three-dimensional printing or directional freezing technology, and only through extremely simple room temperature mechanical foaming and the synergy of the above reaction kinetic control, a layered structure similar to the woody part of a tree (interconnected macropores + dense micropores) is constructed in situ inside the sponge, which perfectly balances capillary suction and extremely low hydraulic resistance from a physical structure perspective.

[0058] (3) Innovation of salt resistance mechanism (spatial transport decoupling): In response to the pain point that existing 3D photothermal evaporators are difficult to handle high salinity fluids, the micro / macropore collaborative network of the present invention realizes spatial decoupling of mass transfer path: the dense micropore walls are specifically responsible for generating strong capillary suction force to supply water upward, while the through three-dimensional macropore network provides unobstructed downward backflow and convection diffusion channels for the local high concentration of salt solution on the surface, realizing true physical structure-level salt resistance crystallization.

[0059] (4) Large-scale preparation does not rely on expensive and complex equipment, and mass production is simple and low-cost.

[0060] Based on the above innovations, the layered porous polymer sponge provided by this invention can be widely used in: Off-grid / distributed seawater desalination: providing core components for low-cost, high-throughput, and maintenance-free solar-powered desalination production for islands and arid coastal areas.

[0061] High-concentration salt lake brine concentration: Utilizing its excellent anti-salt crystallization properties, it achieves rapid concentration of extremely high salinity brine with zero energy consumption.

[0062] Emergency relief and portable water purification: Combining its lightweight, high mechanical toughness and shape memory function, it can be made into portable water purification equipment that unfolds upon contact with water and produces water efficiently.

[0063] The specific embodiments of the present invention described above do not constitute a limitation on the scope of protection of the present invention. Any other corresponding changes and modifications made in accordance with the technical concept of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A method for large-scale preparation of layered porous polymer sponges, characterized in that, Includes the following steps: S1. Mix the first hydrophilic polymer, multifunctional pore regulator, aldehyde crosslinking agent, photothermal conversion material and water evenly to obtain a precursor solution; S2. Mechanically foam the precursor solution to form a stable foam emulsion; S3. Then, an acidic catalyst is added to the foam emulsion, and the emulsion is poured into the mold in batches. S4. In-situ thermosetting crosslinking reaction is carried out in the mold; S5. Obtain a layered porous polymer sponge with interconnected macropores and micropores in the pore walls.

2. The preparation method according to claim 1, characterized in that, In step S1, the multifunctional pore regulator is composed of a second hydrophilic polymer, which is a water-soluble polymer rich in amino groups and is selected from one or more of water-soluble chitosan, polyacrylamide, polyethyleneimine, polyethyleneamine, polylysine, or polyamide-amine dendritic macromolecules.

3. The preparation method according to claim 1, characterized in that, In step S1, the first hydrophilic polymer is selected from one or more of polyvinyl alcohol, cellulose derivatives, or sodium alginate; the photothermal conversion material is selected from one or more of carbon nanotubes, carbon black, graphite powder, graphene oxide, polypyrrole, or pyrrole-2-carboxaldehyde; the aldehyde crosslinking agent is selected from one or more of formaldehyde, glutaraldehyde, or glyoxal; and the acidic catalyst is selected from one or more of sulfuric acid, hydrochloric acid, nitric acid, or acetic acid.

4. The preparation method according to any one of claims 1 to 3, characterized in that, Based on water as 1 part by weight, the addition amounts of each component are as follows: the first hydrophilic polymer is 0.05~0.20 parts by weight; the multifunctional pore regulator is 0.01~0.15 parts by weight; the photothermal conversion material is 0.005~0.1 parts by weight; the aldehyde crosslinking agent is 0.01~0.15 parts by weight; and the acidic catalyst is 0.01~0.3 parts by weight.

5. The preparation method according to claim 1, characterized in that, In step S2, the conditions for mechanical foaming include: a mechanical stirring speed of 8000~20000 rpm; and a mechanical stirring time of 5~30 min.

6. The preparation method according to claim 1, characterized in that, In step S4, the reaction temperature of the in-situ thermosetting crosslinking reaction is 20~80 °C; the reaction time is 1~72 h.

7. The preparation method according to claim 1, characterized in that: After the in-situ thermosetting crosslinking reaction is completed, the process further includes: taking out the obtained sponge and washing it repeatedly with a washing solution until the pH value of the washing solution is neutral, and then drying it.

8. The preparation method according to claim 1, characterized in that, The container for the in-situ thermosetting crosslinking reaction is a mold of various shapes, including cylinders, cones, cubes, or 3D irregular containers. The container material can be polymer, glass, ceramic, or metal. The container volume is upgraded to the cubic level. After the reaction is completed, the container is demolded.

9. A layered porous polymer sponge, characterized in that, The layered porous polymer sponge is prepared by the preparation method according to any one of claims 1 to 8; the sponge has a layered structure in which macropores and micropores are connected, wherein the pore size of the macropores is 100 to 200 μm and the pore size of the micropores is 1 to 3 μm.

10. An application of a layered porous polymer sponge, characterized in that, The layered porous polymer sponge described in claim 9 can be applied to solar interface water evaporation, seawater desalination, or high-salt wastewater treatment.